Developing Language Study Textbooks: An Effort to Understand Discourse Theory Using Basic Literacy Based on Problem Solving Model - Purwati, Panca Dewi; Afifah, Nur Ummi (Journal of Languages and Language Teaching, 2025)
Discourse material and discourse theory are two different studies, but both are important to be mastered by students of the Elementary School Teacher Education Study Program (PGSD) as provisions for becoming professional teachers. The results of the assessment through the ujian.ac.id application show that the average score of students' understanding of discourse theory has not yet reached completion. Based on the needs analysis, it is necessary to develop an Indonesian Language Study textbook as a contextual learning resource that also functions as basic literacy material through habituation, development, and learning activities. This study aims to: describe the results of the textbook validation test, and describe the results of the textbook effectiveness test. The study used the Research and Development (R&D) method of the Borg & Gall model which was simplified into seven stages. The validation results by material experts obtained an average score of 4.27 with the category "very good". The effectiveness test was carried out in two stages, namely small scale and large scale, involving two learning classes that had equivalent characteristics. Based on the results of the large-scale effectiveness test, an increase in learning outcomes of 0.70 was obtained with a moderate category. The novelty of this study lies in the integration of basic literacy in problem-based learning that encourages students to be active and effective in the learning process. Thus, the Indonesian Language Study textbook is effectively used to improve the understanding of discourse theory of PGSD students through the involvement of basic literacy in problem-based learning. Students become more active and are able to utilize learning time effectively through literacy activities facilitated by the developed textbook. The contribution of this research lies in providing PGSD students with a practical and contextual learning resource that not only strengthens theoretical mastery but also enhances critical literacy practices essential for future teachers.